Incidence of superficial venous thrombosis in primary care and risk of subsequent venous thromboembolic sequelae: a retrospective cohort study performed with routine healthcare data from the Netherlands - Geersing, Geert-Jan (BMJ Open, 2018)
OBJECTIVES: Recent studies in referred populations of patients with superficial venous thrombosis (SVT) report risks of venous thromboembolic (VTE) sequelae (deep vein thrombosis or pulmonary embolism) as high as 25%. Likely, these estimates are lower in non-referred patients, but large-scale population-based studies are lacking. We aimed to estimate the incidence rate of SVT in primary care and quantify its risk of VTE sequelae. DESIGN: A retrospective cohort study, using International Classification of Primary Care coding (K94.02) combined with free text searching (synonyms for SVT) to capture all SVT events. All patients were followed up for 3 months using manual free text searching. SETTING: Primary care. PARTICIPANTS: All patients enlisted with general practitioners within the Utrecht General Practitioner Network between 2010 and 2016 (1 534 845 person-years follow-up). MAIN OUTCOME MEASURES: The incidence rate of SVT was expressed as the number of SVT events per 1000 person-years of follow-up and the 3-month cumulative incidence of VTE events was calculated. Logistic regression analysis was used to compare patients with SVT with and without VTE sequelae. RESULTS: A total of 2008 SVT cases were identified, that is, an SVT incidence rate of 1.31 (95% CI 1.25 to 1.37) per 1000 person-years follow-up, with higher rates notably with increasing age. VTE sequelae occurred in 83 patients; 51 at the time of SVT diagnosis and 32 patients during follow-up (total cumulative incidence of 4.1%; 95% CI 3.3% to 5.1%), and were more frequent in those with an active malignancy (OR 2.19; 95% 0.97 to 4.95) and less frequent in those with varicose veins at baseline (OR 0.57, 95% CI 0.34 to 0.94). CONCLUSION: We found an incidence rate of SVT in primary care of 1.31 per 1000 person-years. The risks of VTE sequelae was relatively low at 4.1%, with the highest risk in patients with cancer and in those who experience an SVT in the absence of varicose veins.